THE CORRELATION BETWEEN STUDENTS’ DEPTH AND BREADTH OF VOCABULARY AND READING COMPREHENSION - Adenia, Amirah Nur; Kamsinah,; Rahman, Indah Fadhilah (English Language Teaching for EFL Learners Journal, 2019)
This research aimed at finding out the correlation between depth and breadth of vocabulary and reading comprehension. This research was conducted by using quantitative method with correlational design. Thirty of fifth semester students of English Education Department at Alauddin State Islamic University of Makassar were chosen as the sample of this research. The data was gathered used Word Associates Test, Vocabulary Level Test and reading Test of English as a Foreign Language (TOEFL). To verify the hypotheses, the data were analyzed by using Pearson’s Product Moment Correlation formula. The finding of this research indicated that there was a moderate correlation between depth of vocabulary and reading comprehension with correlation coefficient value was 0.440 > 0.361, and there was also a moderate correlation between breadth of vocabulary and reading comprehension with correlation coefficient value is 0.421> 0.361. Furthermore, the hypothesis testing showed that both of the index value of correlation coefficient (rxy) of 0.440 for depth of vocabulary and 0.421 for breadth of vocabulary were higher than the index value of correlation coefficient of the Product Moment table (rt) of 0.361 which meant that the null hypothesis (H0) was rejected and alternative hypothesis (H1) was accepted. In conclusion, there was a moderate correlation between the depth and breadth of vocabulary and reading comprehension.